The Making of "Silent Wishes" - Tenerife, Alec Justine C. (Animo Repository, 2023)
This project is an exploration of the process of developing visuals for a story by first conceptualizing a plot and then designing well-suited characters and a background for it. The artist-researcher sought to discover how characters and background can be designed in ways that will effectively tell a story through visuals alone. This was done by studying the art and processes of artists Nico Marlet and Ralph Eggleston and then applying learnings into their own work. The project produced two pieces of concept art–one oil painting and one digital illustration–which were displayed in an on-campus exhibit alongside the final character design sheets and draft sketches.